Optical component based temperature measurement in analyte detection devices - Sohrab, Borzu; Cizdziel, Phillip; Yung, Anthony (2004)
Reflectance based methods and devices are provided for determining the concentration of an analyte in a fluid sample. In practicing the subject methods, a fluid sample is applied to a matrix impregnated with a signal producing system. The signal producing system produces a detectable product in an amount proportional to the amount of analyte in the sample. A surface of the matrix is then illuminated and a reflectance measurement is obtained therefrom, generally following a predetermined incubation period. An optical component, preferably the illumination or light detection means, is also employed to obtain a temperature value corresponding to the ambient temperature of the matrix. The analyte concentration of the sample is then obtained from the reflectance measurement using an algorithm that employs the optical component derived temperature value. The subject methods and devices are suited for use in the detection of a variety of different types of fluid analytes, and are particularly suited for use in detecting the concentration of glucose in whole blood.